METODE MASHLAHAH MURSALAH DAN ISTISHLAH (STUDI TENTANG PENETAPAN HUKUM EKONOMI ISLAM) - M Syakroni (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2017)
Marshlahah mursalah and istishlah is a harmonious consideration of ijtihad for the necessities of life today, in accordance with the purpose of syara ', as well as to strengthen the truth, and the universality of Islamic shari'ah, although the text of the Shari'ah itself does not specify. The benefit of human life is the goal of the Shari'ah and all the laws it contains can bring goodness and happiness, whereas the Shari'a rejects all that corrupts creatures.